1981
DOI: 10.1002/1097-0142(19810701)48:1<98::aid-cncr2820480119>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and glucagon secretion by renal adenocarcinoma

Abstract: A patient with histologically verified renal adenocarcinoma had dramatic increases in glucagon and insulin levels in plasma and in tumor tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Many tumours have been reported to be insulin-producing/ secreting in humans, such as: insulinoma (Yoshinobu et al, 1985), cervix carcinoma and corpus uteri carcinoma (Pavelic et al, 1982a), mammary and bronchial carcinoma (Greenberg et al, 1968), thoracic sarcomata and fibrosarcoma (Linscheer et al, 1967), renal adenocarcinoma (Pavelic & Pavelic, 1981). Hodgkin's and non-Hodgkin's lymphoma (Pavelic et al, 1982b;Pavelic & Vuk-Pavlovic, 1983).…”
Section: El4 Tumourmentioning
confidence: 99%
“…Many tumours have been reported to be insulin-producing/ secreting in humans, such as: insulinoma (Yoshinobu et al, 1985), cervix carcinoma and corpus uteri carcinoma (Pavelic et al, 1982a), mammary and bronchial carcinoma (Greenberg et al, 1968), thoracic sarcomata and fibrosarcoma (Linscheer et al, 1967), renal adenocarcinoma (Pavelic & Pavelic, 1981). Hodgkin's and non-Hodgkin's lymphoma (Pavelic et al, 1982b;Pavelic & Vuk-Pavlovic, 1983).…”
Section: El4 Tumourmentioning
confidence: 99%
“…One case noted increased levels of glucagon, which trended down after nephrectomy and presents the possibility of an endocrine mechanism of hyperglycemia (6). Another case detected elevation of anti-glutamic acid dehydroxylase (GAD) and antiislet cell antibodies, which also normalized following nephrectomy and suggested a possible insulin deprivation mechanism due to pancreatic dysfunction on the level of the beta-islet cell (5).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed 7 previously reported cases of RCC with hyperglycemia in the English literature that were available for review (4)(5)(6)(7)(8)(9)(10). Years of publication ranged from 1981 to 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Çoğu hastada nefrektomi sonrası bu bozukluklar ortadan kalkmaktadır. Bu semptomlar tümör hücrelerinden birtakım hormonların salgılanabileceği fikrini akıllara getirmiştir ve yapılan çalışmalarda tümör ekstrelerinde insülin ve glukagon hormonlarına rastlanılmıştır (50 …”
Section: çEşitli Endokrin Anomalilerunclassified